2020
DOI: 10.1097/inf.0000000000003000
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Infection-associated Central Nervous System Disease in Children

Abstract: Background: Adenovirus (Adv) is a frequent etiology of acute respiratory tract infections. Although rare, neurologic manifestations are known to occur during Adv infection. Methods: We retrospectively analyzed clinical, laboratory, outcome and the relationship between clinical characteristics and viral detection results in the cerebrospinal fluid (CSF) in children with Adv-associated central nervous system (CNS) dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Neurological symptoms were associated with adenovirus, which has been observed in other children. 14 In a pediatric cohort with adenovirus infection, a subset (1.5%, 21/1,360) had evidence of encephalitis, encephalopathy, or meningitis. In this subset, 100% (21/21) had encephalopathy, with seizures (9.5%, 3/21), weakness (9.5%, 3/21), gait disturbance (5%, 1/21), and 1 patient (5%) died).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological symptoms were associated with adenovirus, which has been observed in other children. 14 In a pediatric cohort with adenovirus infection, a subset (1.5%, 21/1,360) had evidence of encephalitis, encephalopathy, or meningitis. In this subset, 100% (21/21) had encephalopathy, with seizures (9.5%, 3/21), weakness (9.5%, 3/21), gait disturbance (5%, 1/21), and 1 patient (5%) died).…”
Section: Discussionmentioning
confidence: 99%
“…In this subset, 100% (21/21) had encephalopathy, with seizures (9.5%, 3/21), weakness (9.5%, 3/21), gait disturbance (5%, 1/21), and 1 patient (5%) died). 14 One study using a mouse model with adenoviral infection may shed some light on a potential pathophysiological mechanism for how adenovirus can cause neurological symptoms. This mouse model of neuroinflammation related to adenoviral infection demonstrates hemorrhagic encephalomyelitis, with microglial activation and blood-brain barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented a low incidence of complications and a favorable prognosis for individuals with adenovirus encephalitis. 14,23 Our study revealed that slightly over half of the children did not develop any complications, while nearly 40% experienced complications such as pneumonia or acute bronchitis, followed by myocardial damage. Only a small percentage of children, approximately 1%, suffered from neurological complications such as epilepsy, cerebral hernia, or paralysis.…”
Section: Discussionmentioning
confidence: 68%
“…Adenovirus encephalitis typically presents with symptoms such as fever, headache, convulsions, disturbance of consciousness, and meningeal irritation. In severe cases, the disease may lead to varying degrees of neurological sequelae 14 . This highlights the severity of the disease and the significant threat it poses to children's health.…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus-related central nervous system (CNS) diseases cover a wide range, including meningitis, encephalitis, and encephalopathy. The prognosis of adenovirus-related CNS involvement is usually good [ 6 ], and risk factors associated with adverse clinical outcomes include seizures, coagulopathy, and young age [ 7 ]. No fatal cases of HAdV type 7-related encephalitis have been reported in this decade.…”
mentioning
confidence: 99%